ADOLESCENTES E ALIMENTOS DIET E LIGHT: DEFINIÇÃO, FREQUÊNCIA E RAZÕES PARA O CONSUMO - Daiane Pires da Silva Santos; Maria Luisa de Jesus Barbosa; Janine Vitorasse Delboni; Marcia Lopes Weber (Universidade do Estado do Rio de Janeiro, 2015)
The aim of this study was to characterize diet and light foodconsumption by adolescents from public and private schools andto identify the level of knowledge about the definition, frequencyand reasons for consumption of these foods. A cross-sectionalstudy was conducted with 284 adolescents aged 13-18 years, ofboth sexes, in a public school and a private school in the southof São Paulo/SP. The self-report questionnaire was administeredwith objective questions about the definition of diet and lightfoods, frequency and reasons for consumption. The answersof boys and girls about diet and light food consumption weresimilar for each type of school. Diet and light food consumptionwas higher among adolescents from the private school than thepublic school, both boys and girls. Light food was consumed ingreater proportion than food diet by the adolescents of bothsexes and schools. Public school boys consumed more diet andlight food than girls, which was the opposite in the privateschool. In both schools, frequency of weekly consumption washigher among boys. Although most adolescents of both sexesand schools have marked the correct concept for diet and lightfood, they showed not knowing how to identify differences inthese foods. The most mentioned reason for diet and light foodconsumption by adolescents from both schools and by privateschool girls was health benefits, and for the public school girlswas weight maintenance. DOI: 10.12957/demetra.2015.13918